Review article: a clinician's guide for therapeutic drug monitoring of infliximab in inflammatory bowel disease. Issue 5 (14th July 2013) - Khanna, R.; Sattin, B. D.; Afif, W.; Benchimol, E. I.; Bernard, E.‐J.; Bitton, A.; Bressler, B.; Fedorak, R. N.; Ghosh, S.; Greenberg, G. R.; Marshall, J. K.; Panaccione, R.; et al.
Summary Background Tumour necrosis factor (TNF)‐antagonists have an established role in the treatment of inflammatory bowel diseases (IBDs), however, subtherapeutic drug levels and the formation of anti‐drug antibodies (ADAs) may decrease their efficacy. Aim The evidence supporting the use of therapeutic drug monitoring (TDM) based clinical algorithms for infliximab (IFX) and their role in clinical practice will be discussed. Methods The literature was reviewed to identify relevant articles on the measurement of IFX levels and antibodies‐to‐infliximab. Results Treatment algorithms for IBD have evolved from episodic monotherapy used in patients refractory to all other treatments, to long‐term combination therapy initiated early in the disease course. Improved remission rates have been observed with this paradigm shift, nevertheless many patients ultimately lose response to therapy. Although empiric dose optimization or switching agents constitute the current standard of care for secondary failure, these interventions have not been applied in an evidence‐based manner and are probably not cost‐effective. Multiple TDM‐based algorithms have been developed to identify patients that may benefit from measurement of IFX and ADA levels to guide adjustments to therapy. Conclusions Therapeutic drug monitoring offers a rational approach to the management of secondary failure to IFX. This concept has gained momentum based on evidence from case series, cohort studies and post‐hoc analyses of randomised controlled trials.